On the species of Tulpa Stechow, 1921 (Cnidaria, Hydrozoa) with the description of two new species from sub-Antarctic waters - Cantero, Álvaro Luis Peña (Zootaxa, 2025)
The genus Tulpa Stechow, 1921 is represented by a few species of benthic hydroids that are only occasionally reported. Recently obtained material from various Antarctic and sub-Antarctic localities, together with an exhaustive study of the literature, has allowed me to carry out a revision of the species undoubtedly belonging to the genus, namely Tulpa costata Gravier-Bonnet, 1979, Tulpa diverticulata Totton, 1930 and Tulpa tulipifera (Allman, 1888) and to describe two species new to science, Tulpa peculiaris sp. nov. and Tulpa revelata sp. nov. In addition, several species of uncertain taxonomic status that may belong to Tulpa have been revised based on the literature. These include Campanularia crenata Allman, 1876, Campanularia speciosa Clark, 1877 and Campanularia magnifica Fraser, 1913, which were originally included in Tulpa by Stechow when he established the genus but later excluded by other authors, as well as Campanularia bigena Naumov, 1960.